PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP PERILAKU SISWA DALAM MENGHARGAI KEBERAGAMAN PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SDN 101773 KOLAM KEC. PERCUT SEI TUAN - Zendrato, Putri; Sitohang, Risma; Gandamana, Apiek; Nasution, Yusra; Siregar, Waliyul Maulana (Jurnal Merah Putih Sekolah Dasar, 2024)
The problem underlying this research is that students' behavior still lacks respect for the diversity around them, which can be seen from the way students make friends and interact with their friends. The aim of this research is to determine the effect of the role playing learning model on student behavior in appreciating diversity in class IV Pancasila Education subjects at SDN 101773 Kolam Kec. Percut Sei Tuan. This research uses a quasi-experimental research method and a posttest only control design. The subjects of this research were class IV, totaling 44 students. Data collection uses observation and questionnaires. Data analysis techniques were carried out using descriptive analysis and hypothesis testing. Based on the results of the analysis, the experimental class with the role playing learning model obtained an average score of 78.78, while the control class with the conventional learning model obtained an average score of 72.33. Furthermore, the results of hypothesis testing through the independent t-test of behavior respecting diversity in Pancasila education subjects between the experimental class and the control class obtained a significant level value (2 tailed) < 0.05, namely 0.035. This means that H0 is rejected and Ha is accepted. So it is concluded that the role playing learning model influences students' behavior in appreciating diversity in class IV Pancasila Education subjects at SDN 101773 Kolam, Kec. Percut Sei Tuan. Keywords: Learning Model, Role Playing, Student Behavior, Respect Diversity.